Estudo de otimização de custo em base de compressor para refrigeradores - Maximiano, Raphael Cesar (2021)
This study used tools from the Lean Six Sigma philosophy in order to generate gains through cost reduction for a refrigerator factory. The project was motivated by the necessity for minimizing costs due to COVID19 pandemic crisis and by the need for standardization and optimization of component’s designs. The activities were executed in accordance with the DMADV method that structures the DFSS methodology and, through value analysis and DFMA, it was decided to focus the activities on finding an alternative for the current raw material specification and to internalize assembly for the rollers. Those actions generated little less than 8% reduction of component’s total cost with a 4-month payback time. Due to restrictions on time, resources, and people there are still actions being deployed. Nevertheless, there are more potential savings than the ones listed. This study helped to identify similar opportunities in other factories that can result in new actions for minimize costs using relatively lower investment.